A Bibliometric Analysis and Overview: A Study to Understand the Trend of Sustainable Logistic Studies in Malaysia (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract Background: Nowadays, business organization implementing the Sustainable Development Gold (SDG) in their business operations and company policy as their support towards sustainability. Sustainable logistic is supporting the United Nations Sustainable Development Goals (SDGs) aim to improve economic, social, and environmental outcomes through increased efficiency, lower emissions, and improved resource management. It helps to achieve goals such as sustainable energy (SDG 7), responsible production and consumption (SDG 12), infrastructure (SDG 9), and fewer traffic accidents (SDG 3). Key factors include developing green energy applications, streamlining supply chains, supporting sustainable procurement, and utilizing technologies such as artificial intelligence and blockchain to improve supply chain sustainability and performance. This study aims to understand the trend of sustainable logistic studies, key theme, publication trend and citation, authors, and co-word related to sustainable logistic. This study will provide an insight to for future study on sustainable logistic.Method: A bibliometric analysis is use in this study by extracting data from Dimension.Ai database. By using three keyword which are ‘Sustainable’ AND ‘Logistic’ AND ‘Malaysia’. Performance analysis, science mapping network analysis use in this study.Result: Publication trend show that the post-peak trend suggests that while the initial fervour may have subsided, the topic continues to be a subject of ongoing, albeit less intensely focused, academic inquiry. The frequent number of authors are 3 to 5 people. Co- words analysis show how the topic being choose and discuss within the industry. This topic become matured and more analysis needed for the future studyConclusion: Base on the bibliometric analysis, we can conclude that the field of telematic system acceptance is a dynamic and deeply interconnected research area. The densest clusters demonstrate that the study has expanded beyond the individual user to encompass the broader system performance, transport efficiency, and industry-level integration.